Abnormal Uterine Bleeding and External Genital Endometriosis in a 14-Year-Old Patient with Idiopathic Thrombocytopenic Purpura: Case Report - Elena V. Sibirskaya; Irina V. Karachentsova; Aliya Yu. Kurmangaleeva; Aina S. Annakulieva (Педиатрическая фармакология, 2025)
Background. Idiopathic Thrombocytopenic Purpura is one of the most common acquired blood-clotting disorders in adolescents. This disease is characterized by an increased risk of developing concomitant gynecological pathologies, such as abnormal uterine bleeding, ovarian tumors and tumor-like masses, external genital endometriosis, which requires careful medical supervision and, if necessary, surgical intervention. Case report. A clinical event of a 14-year-old patient with idiopathic thrombocytopenic purpura complicated by external genital endometriosis and abnormal uterine bleeding is being considered. The patient underwent surgery in the amount of laparoscopic oophorectomy, which prevented the development of severe complications. Conclusion. This case gives accent to the importance of a comprehensive and interdisciplinary approach to the treatment of patients with idiopathic thrombocytopenic purpura and concomitant gynecological pathologies, which helps minimize the risk of life-threatening complications.